FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KADER DALAM PELAKSANAAN POSYANDU LANSIA DI KELURAHAN SENDANGMULYO KECAMATAN TEMBALANG KOTA SEMARANG - Rini Oktaviani Handayani; Antono Suryoputro; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Neighborhood Health Centers (Posyandu) for Elderliesis is a government’s policy to serve the elderly population whose process of formation and implementation is done by the community with emphasis on promotive and preventive efforts. Health service in Semarang City is 52, 81%, still below Minimum Service Standard (SPM) of 70%. In the elderly posyandu activities, cadres have an important role as health service providers. If the cadres not working properly it will affect the posyandu elderly every month. Based of researchers observation, known 4 of 5 posyandu in Sendangmulyo not implemented 5 posyandu table system optimally. The purpose of this study to determine the factors associated with the practice of cadres in Sendangmulyo, Semarang City. The type of research is analytical with cross sectional study approach. Research subjects 63 elderly posyandu cadres in Sendangmulyo. The statistical test used to analyze the relationship between variables using Chi Square.Based on the result of the research, the variables that have good appraisal are practice (63.4%), knowledge (69,8%), attitude (57,1%), training (65,1%), infrastructure (55,4%), access (82,5%) , supervision (52.4%), and health support (61.9%). While the variables that have poor ratings are motivation (52,4%) and incentives (54%).There were significant correlation between respondent education (p = 0,000), respondent's knowledge (p = 0,003), respondent attitude (p = 0,000), respondent motivation (p = 0,000), incentive (p=0,005), infrastructure facilities (p = 0,000), supervision (p = 0,003) , and health officer support (p = 0,000) with cadre practice in the implementation of posyandu elderly in Sendangmulyo Semarang. While unrelated variables are age, training, and access.It is expected that the puskesmas can improve the motivation and ability of cadres in conducting counseling to the elderly and expected the kelurahan can improve the facilities and infrastructure of election and cadres.